Efektifitas Proses Mediasi Dalam Perkara Perceraian Di Pengadilan Agama Padang - Miasiratni Miasiratni; Widya Yoseva; Suci Nurjannah Yuansyah; Nofrisca Patma Witri (Universitas Sumatera Barat, 2025)
This study aims to analyze the effectiveness of the mediation process in resolving divorce cases at the Padang Religious Court and identify factors influencing the success and failure of mediation. The research method used is empirical legal research with a qualitative approach. Data were obtained through interviews with the mediator judge and the parties, as well as a study of divorce case documents that have undergone mediation at the Padang Religious Court. The collected data were analyzed descriptively qualitatively by linking applicable legal provisions with their implementation in practice. The results indicate that the mediation process in divorce cases at the Padang Religious Court has not been fully effective in reducing the divorce rate. This is due to the parties' low good faith in reconciliation, long-standing domestic conflicts, and limited time for mediation. Nevertheless, mediation remains an important means of communication and clarification between husband and wife before the case is decided by the judge. Therefore, it is necessary to optimize the role of the mediator and increase the awareness of the parties so that the objectives of mediation can be optimally achieved.